Transcranial Doppler Imaging; A simple Guide for Brain Death Before CT Angiography - YILDIZ ÜSTÜN, BETÜL; KASAPOĞLU, UMUT SABRİ; GÜL, FETHİ (My University, 2023)
Introduction: Ancillary tests can be used for the diagnosis of brain death in cases wherein uncertainty exists regarding the neurological examination and apnoea test cannot be performed. Transcranial Doppler ultrasonography (TCD) is a useful, valid, non-invasive, portable, and repeatable ancillary test for the confirmation of brain death. The purpose of this case is to represent the utility of transcranial Doppler as an ancillary test in brain death confirmation. Case: A 32-year-old male patient was admitted to intensive care unit after DSA intervention due to middle cerebral artery (MCA) aneurysm. In the intensive care follow-ups, sedation vacation attempted, however his brain stem reflexes were absent, he had no respiratory effort, GCS score was 3, pupils were fixed dilated. The patient’s hemodynamic status remained stable throughout the ICU stay, only requiring low-dose norepinephrine for less than 12 hour. Neurological examination showed the absence of the corneal, gag, oculovestibular, and cough cranial reflexes. The apnea test was positive and then secondly TCD performed. Cerebral blood flow cessation detected and oscillating flow waves observed in MCA, anterior cerebral artery (ACA), posterior cerebral artery (PCA), basilar and vertebral arteries. We determined when to perform CT angiography (CTA) with light of TCD. Brain death was confirmed according to CTA results. Discussion: TCD ultrasonography, one of the ancillary bedside tests for brain death, is a non-invasive, reproducible method. Despite its limitations, TCD helps solve common diagnostic problems, avoids the unnecessary consumption of resources. It is inevitable that intensivists will gradually increase the use of TCD ultrasonography in the diagnosis of brain death in the near future due to its advantages. Keywords: Transcranial doppler USG, brain death, CT angiography, cerebral blood flow
Keywords: Transcranial doppler USG; brain death; CT angiography; cerebral blood flow